DAMPAK KESIAPAN MAHASISWA DALAM MENGAMBIL MATA KULIAH PEMBIMBING DAN TEOLOGI PERJANJIAN BARU TERHADAP HASIL BELAJAR - Pujiati (JURNAL PENABIBLOS, 2019)
One of the objectives of this research is to understand how far students are prepared to take the New Testament Theology. This subject is so important because it can lead students to be directed to have a good life and they can grow in God. In studying theology too, every believer comes to understand the purpose of God in His Word which is about the great saying "Go therefore, make disciples of all nations and baptize them in the name of the Father, and of the Son and of the Holy Spirit, and teach them to do all something that I have commanded you. And know, I am with you always to the end of time. " This research will use survey method. For this study the authors took a survey study with descriptive methods. This method is carried out to measure certain social phenomena, then explained descriptively or narratively. To measure success here, the writer will use a tool that is the Presence first. Second, is the Test to memorize Verses. Third, the Shock Test (Pop Test). Third, a small test of the New Testament. Fourth, work on the Scriptures (grades as TTS), and fifth, End of Semester Tests. The results of the study are expected to contribute positively to students who take the New Testament Theology, so that with this research, they maximally attend this lecture and obtain maximum results as well.